Analisis Kinerja Keuangan Ditinjau Dari Aspek Rasio Likuiditas Dan Rentabilitas Modal PT. Pajjaiang Indah Makassar - Mardiana Ibrahim; Muhtazib Muhtazib; Hasmawati Hasmawati (CEMERLANG : Jurnal Manajemen dan Ekonomi Bisnis, 2021)
The purpose of this research is to determine the financial performance of PT. Pajjaiang Indah in terms of the ratio of liquidity and profitability of own capital in 2017-2019. The liquidity ratios used in this study are the current ratio, the quick ratio, and the cash ratio. And the profitability of own capital. The research method used is descriptive qualitative, and uses the type of secondary data which is data that has been processed in the form of financial reports sourced from PT. Pajjaiang Indah which consists of a profit and loss statement and balance sheet from 2017-2019. The results of the analysis of the financial performance of PT. Pajjaiang Indah Makassar, in terms of the liquidity ratio aspect from 2017-2019, using the Current Ratio calculation, the liquidity level shows an average of 1.82 times or 182% of the standard 2 times or 200%, this means the level of liquidity at PT . Pajjaiang Indah in terms of the Current Ratio (Current Ratio) is declared illiquid. Meanwhile, in terms of the Quick Ratio aspect, it shows an average of 1.69 times or 169% from the standard 1.5 times or 150%, this means that the liquidity level of PT. Pajjaiang Indah in terms of the Quick Ratio aspect is declared liquid. And viewed from the aspect of the Cash Ratio (Cash Ratio) shows an average of 0.24 times or 24% of the standard 1 time or 100%, this means the level of liquidity of PT. Pajjaiang Indah in terms of the Cash Ratio aspect is declared illiquid. From the description of the three aspects of the liquidity ratio, it can be concluded that the level of liquidity of PT. Pajjaiang Indah in 2017 – 2019 was low. From the results of the analysis of the profitability ratio of its own capital, PT. Pajjaiang Indah in 2017 - 2019 obtained an average calculation of 24% from the standard 40%, it can be concluded that the average level of profitability of PT. Pajjaiang Indah in 2017 – 2019 was low.